THU0333 Chronological Analysis of Damage Accrual in SLE Patients from The spanish Registry (RELESSER). (15th July 2016) - Pego, J.; Lois, A.; Mouriño, C.; L-Longo, F.; Galindo, M.; Calvo, J.; Uña, J.; Balboa, V.; Olive, A.; Otόn, T.; Ibañez, J.; Horcada, L.; et al.
Abstract : Background: Mortality in SLE has improved over the last decades. Outcome measures as damage become more important. Objectives: To study damage manifestations and the timing of their appearance. Methods: In the 1st transverse phase of RELESSER, accumulated information on 400 variables per patient at the time of the last evaluation was collected. We evaluated damage manifestations in each system and the temporal relationship of their appearance with the time of SLE diagnosis. Cumulative incidence function for damage was estimated.The impact on mortality was studied controlling for sex, race, age at diagnosis and delay of diagnosis of SLE by Cox regression. Results: 2, 662 SLE patients had the dates of presentation of each event of damage: 2, 417 (91.0%) women, 2, 402 (92.8%) Caucasian, mean age (±SD) 34.0 (±13.6) years at the time of diagnosis. The mean follow-up time was 115.6 (±50.8) months. 112 (4.2%) patients died. At the time of the study 917 (34.4%) patients had at least 1 damage manifestation, the mean number of systems per patient with at least 1 damage manifestation was 0.54 (±0.92) and the mean SDI score was 0.65 (±1.2). The systems more frequently damaged were musculoskeletal (MS) (11.9%), ophtalmic (7.8%) and cardiovascular (CV) (5.9%).In the 1st year after SLE diagnosis, the cumulative incidence (CI 95%) of damage in at least 1 system was 7.4% (6.4–8.4), at 5 years 18.9% (17.3–20.4) and after more than 10 years 29.2% (27.3–31.1).The systems damaged at earliest stages, 1 year after SLE diagnosis, were: MS 1.7% (1.2–2.2), neuropsychiatric 1.3% (0.8–1.7), renal 1.2% (0.8–1.6) and CV 0.9% (0.6–1.3). The rate of increase of damage is significantly higher (p<0.001) short time after SLE diagnosis. The proportion of patients with damage in at least 1 system at 5 and 10 years was 18.9% (17.3–20.4) and 29.2% (27.3–31.1). While in the 1st year 7.4% of patients present damage in any system, only 2.9% per year do so since the 1st to the 5th year after diagnosis and, between the 5th and 10th year there was only an annual increase of damage of 2.1%.Risk of death is multiplied by 2.04 (1.7–2.3) at the time that a new system is damaged. Significant impact on neuropsychiatric, renal, pulmonary, CV systems and malignancy was found, with multiplicative risk factors of 2.0, 1.8, 2.8, 1.7 and 2.7 respectively. Conclusions: Damage occurs already in early stages of the disease. It appears early in MS, neuropsychiatric and kidneys. The increase of damage is greater in the 1st year after SLE diagnosis. The accumulation of visceral damage increases the mortality rate. Disclosure of Interest: J. Pego Grant/research support from: Spanish Society of Rheumatology, FIS/ISCIII (PI11/02857), BIOCAPS from the EU 7th Framework Programme/REGPOT-2012–2013.1 (316265), GSK, Roche, Novartis, UCB., A. Lois: None declared, C. Mouriño: None declared, F. L-Longo: None declared, M. Galindo: None declared, J. Calvo: None declared, J. Uña: None declared, V. Balboa: None declared, A. Olive: None declared, T. Otόn: None declared, J. Ibañez: None declared, L. Horcada: None declared, A. Sánchez: None declared, C. Montilla: None declared, R. Melero: None declared, V. MTaboada: None declared, E. Diez: None declared, M. Fernandez: None declared, E. Ruiz: None declared, J. HBeriain: None declared, M. Gantes: None declared, B. HCruz: None declared, A. Pecondon: None declared, N. Lozano: None declared, G. Bonilla: None declared, V. Torrente: None declared, L. Silva: None declared, A. FNebro: None declared, I. Rua: None declared